2013
DOI: 10.1136/jech-2013-203402
|View full text |Cite
|
Sign up to set email alerts
|

Age of first drinking and adult alcohol problems: systematic review of prospective cohort studies

Abstract: BackgroundAlcohol policies around the world seek to delay the initiation of drinking. This is partly based on the influential idea that earlier initiation is likely to cause adult alcohol problems. This study synthesises robust evidence for this proposition.MethodsSystematic review of prospective cohort studies in which adolescent measurement of age of first drink in general population studies was separated by at least 3 years from adult alcohol outcomes. EMBASE, Medline, PsychINFO and Social Policy and Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 31 publications
4
86
0
Order By: Relevance
“…Although there is a vast amount of research suggesting that adolescent alcohol consumption is a strong predictor of alcohol problems in adulthood, the underlying mechanisms of the relationship is not understood fully 16, 25. From a life‐course perspective, adolescence can be considered a sensitive time‐period where individuals are more vulnerable to various social and biological exposures, which can have an impact on health later in life 14, 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a vast amount of research suggesting that adolescent alcohol consumption is a strong predictor of alcohol problems in adulthood, the underlying mechanisms of the relationship is not understood fully 16, 25. From a life‐course perspective, adolescence can be considered a sensitive time‐period where individuals are more vulnerable to various social and biological exposures, which can have an impact on health later in life 14, 38.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests that individuals consuming alcohol already in early adolescence are more vulnerable to the long‐term health consequences compared to individuals who begin consuming alcohol in late adolescence 25, 26, 27, 28. Further, evidence suggests that the consequence of consuming alcohol is more severe among those with lower socio‐economic status 29, 30, but little is known about the potential differential responsiveness to a decrease in the legal age limit for alcohol purchases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 21 definitions described by Kuntsche et al [1], most of them attempt to characterize consumption as 'bigger than a few sips'. However, the only systematic review including prospective studies that used this AFD definition found only five studies, and concluded that there are insufficient data to draw definitive conclusions about the relationship between AFD and AD in adults [4]. In other words, there is need to reach a consensus within the scientific community about what is, and how to evaluate, AFD.…”
Section: Usefulness Of Afd Concept: Limitations To Overcomementioning
confidence: 99%
“…Rather than being a fatal weakness, the replication of those relations using a variety of terms suggests a robust association, which has been found in cross-sectional surveys [4][5][6], in some [7][8][9][10][11] but not all [12] longitudinal studies and studies that control for genetics [13], such as studies of identical twins [14].…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Rather than being a fatal weakness, the replication of those relations using a variety of terms suggests a robust association, which has been found in cross-sectional surveys [4][5][6], in some [7][8][9][10][11] but not all [12] longitudinal studies and studies that control for genetics [13], such as studies of identical twins [14].…”
Section: The Usefulness Of 'Age At First Drink' As a Concept In Alcohmentioning
confidence: 99%